Temporal Variation of Atmospheric Fossil and Modern CO2 Excess at a Central European Rural Tower Station between 2008 and 2014. Issue 5 (19th September 2018) - Major, István; Haszpra, László; Rinyu, László; Futó, István; Bihari, Árpád; Hammer, Samuel; Jull, A J Timothy; Molnár, Mihály
Abstract: In 2008, the atmospheric CO2 measurements at the Hegyhátsál rural tower station were extended further by 14 CO2 air sampling from two elevations (115 and 10 m a.g.l.), in cooperation with HEKAL (ICER). Since then, a complete six-year-long (2008–2014) dataset of atmospheric CO2, Δ 14 C, fossil, and modern CO2 excess (relative to Jungfraujoch) has been assembled and evaluated. Based on our results, the annual mean CO2 mole fraction rose at both elevations in this period. The annual mean Δ 14 CO2 values decreased with a similar average annual decline. Based on our comparison, planetary boundary layer height obtained by modeling has a larger influence on the variation of mole fraction of CO2 (relative to Jungfraujoch), than on its carbon isotopic composition, i.e. the boundary layer rather represents a physical constraint. Fossil fuel CO2 excess at both elevations can rather be observed in wintertime and mainly due to the increased anthropogenic emission of nearby cities in the region. The mean modern CO2 excess at both elevations was even larger in winter, but it drastically decreased at 115 m by summer, while it remained at the winter level at 10 m.